Renal Profile of patients Diagnosed with Corona Virus Disease (Covid-19) admitted in Tertiary Care Hospital - Huma Amin, Fatima Tur Zuhra, Nadia Wali, Farhana Shaukat, Muhammad Sohail Aslam, Atika Masood (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the baseline renal profile of patients with COVID-19. Methods: It was a cross sectional study, conducted in hospitals of Rawalpindi Medical University from March to August 2020. Consecutive 169 confirmed cases of COVID-19 were enrolled. Patients with history of kidney disease were not included. Peripheral blood samples were analysed for renal functions on fully automated chemistry analyser. Estimated glomerular filtration rate (eGFR) for every patient was calculated using two equations for chronic kidney disease epidemiology collaboration (CKD-EPI) and modification of diet in renal disease (MDRD). Results: Out of total 169 COVID-19 patients, 97(57%) were males 72(43%) were females. The mean age was 54.1±16.30 (18 to 92) years. A total of 96(57%) patients were below 60 years of age. Mean Urea, serum creatinine (Scr) and blood urea nitrogen (BUN) were found to be elevated in this study cohort with no statistically significant difference with respect to age and gender (P value >0.05). Scr was raised in 46(27%) while 113(67%) and 103 (62%) patients had elevated serum Urea and BUN respectively. eGFR of <60mL/min/1.73m2 was observed in 50(30%) of patients. Conclusion: Elevated mean Urea, Scr and BUN were observed in COVID 19 patients without any significant difference according to age and gender. Moderate to severe derangement in eGFR was noted in one third of COVID 19 patients.